2022
DOI: 10.1101/2022.04.25.489339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircEML1 facilitates the steroid synthesis in follicular granulosa cells of chicken through sponging gga-miR-449a to release IGF2BP3 expression

Abstract: Non-coding RNAs (ncRNAs) induced competing endogenous RNAs (ceRNA) play crucial roles in various biological process by regulating target gene expression. However, the studies of ceRNA networks in the regulation of ovarian ovulation process of chicken remains deficient compared to that in mammals. In the present study, it was revealed that circEML1 was differential expressed in hen’s ovarian tissue at different ages (15W, 20W, 30W and 68W) and identified as a loop structure from EML1 pre-mRNA, which promoted th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In recent years, many studies have reported that noncoding RNAs, such as miRNAs, lncRNAs and circRNAs, play major roles in the regulation of the reproductive function of laying hens [ 16 , 17 , 18 , 19 , 20 ]. MiRNA is a kind of noncoding small 22 nt RNA that mostly regulates gene expression at the post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have reported that noncoding RNAs, such as miRNAs, lncRNAs and circRNAs, play major roles in the regulation of the reproductive function of laying hens [ 16 , 17 , 18 , 19 , 20 ]. MiRNA is a kind of noncoding small 22 nt RNA that mostly regulates gene expression at the post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we predicted that gga-miR-449b-5p might be involved in the regulation of proliferation and steroid synthesis in ovaries of hens via transcriptome sequencing analysis of hen ovarian tissue during the four classic physiological periods (15 w, 20 w, 30 w, and 68 w), which represent initial ovarian development, sexual maturation, the peak laying period and the late laying period [ 42 ]. In another previous study, we predicted that IGF2BP3 may be its targeted regulatory gene [ 20 ]. At present, the reports on this gene are mainly focused on cell development, proliferation and migration [ 43 , 44 ], especially in cancer development and progression [ 45 , 46 , 47 ], but there are few reports on the reproduction of laying hens.…”
Section: Introductionmentioning
confidence: 99%